2013
DOI: 10.1007/s10067-013-2167-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of managed care health insurance system for indigent patients with rheumatoid arthritis in Puerto Rico

Abstract: The aim of this study was to determine the clinical outcome among indigent patients with rheumatoid arthritis (RA) in Puerto Rico receiving their healthcare in a managed care system, as compared to non-indigent patients treated in fee-for-service settings. A cross-sectional study was conducted in 214 Puerto Ricans with RA (per American College of Rheumatology classification criteria). Demographic features, health-related behaviors, cumulative clinical manifestations, disease activity (per Disease Activity Scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Previous studies have provided evidence of disparities in RA treatment in the Puerto Rican population [9,10]. A cross-sectional study of Puerto Ricans with RA looked at disparities between those receiving their healthcare in a managed care system (n = 67) and non-indigent patients treated in fee-for-service settings (n = 147) [10]. Patients in the managed care setting had more joint deformities, extra-articular manifestations, arterial hypertension, type Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have provided evidence of disparities in RA treatment in the Puerto Rican population [9,10]. A cross-sectional study of Puerto Ricans with RA looked at disparities between those receiving their healthcare in a managed care system (n = 67) and non-indigent patients treated in fee-for-service settings (n = 147) [10]. Patients in the managed care setting had more joint deformities, extra-articular manifestations, arterial hypertension, type Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although arthritis is one of the most prevalent health conditions in Puerto Rico [8], few studies have been conducted in Puerto Rican or Hispanic populations specifically [9][10][11]. Studies in the broader US population have identified some racial and ethnic disparities, reporting higher levels of disease activity and worse functional status in Hispanic patients compared with white patients, although it is not clear why this is the case [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our cohort of RA patients has been described in detail before [ 12 , 13 ]. In short, all patients met the 1987 ACR classification criteria for RA [ 14 ] and had Puerto Rican ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…As described before, our database comprises variables from the demographic, health-related behaviors, clinical, and pharmacologic domains [ 12 , 13 ]. Demographic features and health-related behaviors included age (at study visit), sex, disease duration (time interval between RA onset and study visit), and current status (within the past 30 days) of cigarette smoking, alcohol consumption and exercise.…”
Section: Methodsmentioning
confidence: 99%